Cardiopulmonary bypass for resection of pancoast tumor with mediastinal extension and involvement of right bronchial branch: A case report. (November 2021) - Marzban-Rad, Saeid; Sattari, Parastesh; Marzban-Rad, Maryam; Azimi, Ghasem
Abstract: Introduction: and importance: Pneumonectomy is commonly associated with cardiopulmonary complications. Pneumonectomy in Pancoast tumor with mediastinal extension and no metastasis could be successful and efficient. Case presentation: Herein, we report a successful pneumonectomy of a 54-year-old man with pancoast tumor along with the involvement of mediastinal space including right hilum of the lung, right bronchial, inferior vena cava vein and pericardium. Clinical discussion: Based on the bronchoscopy and biopsy, the complete involvement of right bronchial tree was reported and non-small cell carcinoma was diagnosed in pathology. Conclusion: To reduce the complications of the surgery, the cardiopulmonary pump machine was used during the operation. Highlights: The role of Pneumonectomy to commonly associated with cardiopulmonary complications. Pneumonectomy in pancoast tumor with mediastinal extension and no metastasis. Pneumectomy is with low 5-year survival rate, especially in the case of extended excision. We report a successful pneumonectomy of a 54-year-old man with pancoast tumor.